2022
DOI: 10.1111/jdv.18439
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the most visible websites on cutaneous T‐cell lymphoma—revealing limited quality of patient health information on the internet

Abstract: Background Patients diagnosed with cancer frequently search the Internet for health information. Yet, the quality of CTCL online information has not been investigated so far. Objectives The aim of this study was to identify and assess the most visible websites on CTCL. Methods An Internet search on the top three search engines Google, Yahoo and Bing was performed for the terms ‘cutaneous T‐cell‐lymphoma’, ‘mycosis fungoides’ and ‘Sézary syndrome’. After selecting the most frequented websites suitable for patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…To our knowledge, this was the first study to evaluate the quality and readability of WPAs concerning cancer. Our study mirrored other studies' findings on various topics [22][23][24].…”
Section: Principal Findingssupporting
confidence: 91%
“…To our knowledge, this was the first study to evaluate the quality and readability of WPAs concerning cancer. Our study mirrored other studies' findings on various topics [22][23][24].…”
Section: Principal Findingssupporting
confidence: 91%
“…Like YouTube, many reviewers found a trend of misinformation, high variability, and low readability on websites. The readability scores of sampled skin cancer websites averaged at the high school level, whereas the recommended readability score for medical information is at the seventh-grade level [ 114 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study found varying quality and popularity of websites, noting highly accessed websites tended to provide reliable patient information. 14 Accuracy of patient-oriented education may be assessed in future investigations. Additionally, the geolocation of a Google search impacts results.…”
Section: Discussionmentioning
confidence: 99%